Spatiotemporal evolution and driving factors of the coupling coordination between county land urbanization and grain production: the case of Jiangsu province, China - Chen, Xi; Zhou, Junting; Xing, Lirong; Wang, Haitao; Lu, Jianzhen (Frontiers in Ecology and Evolution, 2023)
How to ensure a coordinated development between land urbanization and grain production has been a key issue that needs to be urgently addressed to achieve sustainable development in China. Taking Jiangsu Province as an example, this paper measures the coupling coordination degree (CCD) between county land urbanization and grain production from 2010 to 2020 based on the coupling coordination degree model (CCDM). In addition, the exploratory spatial data analysis method and the space Durbin model are combined to explore the spatial correlation and influencing factors of the CCD between land urbanization and grain production. The main conclusions are as follows: (1) From a temporal perspective, the CCD between county land urbanization and grain production in Jiangsu is dominated by basically coordinated, with an overall stable rising trend and a distribution pattern of Northern Jiangsu > Central Jiangsu > Southern Jiangsu. (2) From the perspective of spatial distribution, the CCD between the two is dominated by basically coordinated in the Southern, Central and Northern Jiangsu regions. The spatial clustering characteristics are significant, and the distribution of counties with basically coordinated shows concentrated and contiguous characteristics. (3) From the perspective of spatial correlation, the CCD between the two shows a low level of positive spatial autocorrelation. The state of agglomeration is significant in Northern Jiangsu, while spatial agglomeration is sporadic in Southern Jiangsu and insignificant in Central Jiangsu. (4) Per capita GDP and chemical fertilizer application intensity have a negative effect on the CCD between land urbanization and grain production. Highway network density and mobile internet penetration rate have a positive effect on it. This study offers useful insights for promoting the coupled and coordinated development of county urbanization and grain production in China.